"ΦΑΝΤΑΣΙΑΚΕΣ ΚΟΙΝΟΤΗΤΕΣ" ΚΑΙ ΜΕΓΑΛΗ ΙΔΕΑ. ΜΙΑ ΣΥΜΒΟΛΗ TOΥ Ν. Γ. ΠΟΛΙΤΗ - ΒΑΡΟΥΞΑΚΗΣ ΓΕΩΡΓΙΟΣ (Μνήμων, 1991)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><span style="font-size: 10.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EL; mso-fareast-language: EL; mso-bidi-language: AR-SA;">Δεν παρατίθεται περίληψη<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>